2020
DOI: 10.1016/j.siny.2020.101078
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen metabolism and oxygenation of the newborn

Abstract: The premature infant is to some extent protected from hypoxia, however defense against hyperoxia is poorly developed. The optimal assessment of oxygenation is to measure oxygen delivery and extraction. At the bedside PaO 2 and SpO 2 are approximations of oxygenation at the tissue level. After birth asphyxia it is crucial to know whether or not to give oxygen supplementation, when, how much, and for how long. Oxygen saturation targets in the delivery room have been studied, but the optimal targets might still b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 75 publications
(82 reference statements)
1
10
0
Order By: Relevance
“…We found that the increase in oxygen delivery for lambs resuscitated in 100% FiO 2 was not matched by an increase in oxygen consumption following ROSC to compensate for an accumulated oxygen deficit. In contrast to normal conditions where oxygen delivery in a newborn is approximately 3 times higher than consumption, as corroborated at the fetal and post-hyperaemic time points, we found oxygen delivery to be up to 8 times higher than consumption in the 15 min after ROSC 33 . Our findings are consistent with those of neonatal calf and lamb studies that were performed days after birth, well after the transitional period had occurred 34,35 .…”
Section: Discussionsupporting
confidence: 70%
“…We found that the increase in oxygen delivery for lambs resuscitated in 100% FiO 2 was not matched by an increase in oxygen consumption following ROSC to compensate for an accumulated oxygen deficit. In contrast to normal conditions where oxygen delivery in a newborn is approximately 3 times higher than consumption, as corroborated at the fetal and post-hyperaemic time points, we found oxygen delivery to be up to 8 times higher than consumption in the 15 min after ROSC 33 . Our findings are consistent with those of neonatal calf and lamb studies that were performed days after birth, well after the transitional period had occurred 34,35 .…”
Section: Discussionsupporting
confidence: 70%
“…Antioxidative capacity is constituted by superoxide dismutases, catalases, heme oxygenases, flavin-containing enzymes, glutathione, and thioredoxin, which are the most prominent and best-studied candidates. This makes preterm infants especially vulnerable to ROS-induced injury [ 47 ]. The most relevant features of ROS tissue injury, following their accumulation, are ascribed to oxidative damage to proteins, lipids, and DNA [ 48 ].…”
Section: Ros-induced Injury To the Immature Lung As A Key Driver Of Bpdmentioning
confidence: 99%
“…In this review, we summarize recent findings with respect to the association between hyperoxemia and outcomes in critically ill pediatric patients. For an in-depth review of oxygen physiology in premature infants and in the delivery room, the reader is directed elsewhere (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%